2017
DOI: 10.1016/j.dcn.2017.03.006
|View full text |Cite|
|
Sign up to set email alerts
|

Diurnal cortisol after early institutional care—Age matters

Abstract: Several studies have shown that young children who have experienced early caregiving adversity (e.g. previously institutionalization (PI)) exhibit flattened diurnal cortisol slopes; however, less is known about how these patterns might differ between children and adolescents, since the transition between childhood and adolescence is a time of purported plasticity in the hypothalamic-pituitary-adrenal (HPA) axis. PI youth experience a massive improvement in caregiving environment once adopted into families; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 34 publications
5
26
0
Order By: Relevance
“…Although the current analyses focused on morning levels only, diurnal salivary cortisol was measured across 2 consecutive (or close to consecutive) days (for analyses of the full diurnal cycle, see Flannery et al, 2017). Parents were asked to collect saliva across four different times of the day (at wake-up, 45 min after wake-up, at 5 p.m., and at 8 p.m.) for 2 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the current analyses focused on morning levels only, diurnal salivary cortisol was measured across 2 consecutive (or close to consecutive) days (for analyses of the full diurnal cycle, see Flannery et al, 2017). Parents were asked to collect saliva across four different times of the day (at wake-up, 45 min after wake-up, at 5 p.m., and at 8 p.m.) for 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…The interassay coefficient for cortisol was below 8% (Kirschbaum & Hellhammer, 2000). Because several studies have shown that PI samples are likely to differ most in morning values of cortisol (e.g., Flannery et al, 2017; Koss, Mliner, Donzella, & Gunnar, 2016), the current study focused on morning values; this was computed by taking the natural log of the mean of the morning collections (wake-up and wake-up+45 min) across the 2 days. No extreme observe values were found within this sample; therefore, all data points were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…That said, differences between adopted and nonadopted children often remain. A growing number of studies indicate that children or adolescents who have been adopted internationally exhibit atypically low cortisol levels upon wake-up and/or blunted declines in cortisol levels throughout the day (Flannery et al, 2017; Johnson, Bruce, Tarullo, & Gunnar, 2011; Koss et al, 2014; Leneman, Donzella, Desjardins, Miller, & Gunnar, 2018; Quevedo, Johnson, Loman, LaFavor, & Gunnar, 2012; for a review, see Gunnar & Reid, 2019). For at least some individuals adopted internationally, the consequences of the early experiences of adversity for diurnal HPA axis activity persist into adulthood (Kumsta et al, 2017; van der Vegt, van der Ende, Kirschbaum, Verhulst, & Tiemeier, 2009).…”
Section: Diurnal Hpa Axis Activity Among Children Adopted Internationallymentioning
confidence: 99%
“…In contrast, young children living in institutional environments often exhibit lower wake-up cortisol levels and flatter diurnal declines than children being raised by their birth parents (Carlson & Earls, 1997; Chernego et al, 2019). These atypical patterns of HPA axis regulation can persist after children are adopted and placed into highly enriched family contexts (Flannery et al, 2017; Koss, Hostinar, Donzella, & Gunnar, 2014), and they can increase the risk for behavioral problems among children adopted internationally (Koss et al, 2014).…”
mentioning
confidence: 99%